Changes in eccentric hamstring strength and muscle soreness in younger and older male football players following match play - Kepir, E.; Owen, J. A.; Karatay, G. M.; Car, B.; Akaras, E.; Yildirim, N. U.; Yagiz, G. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Introduction Hamstring strains commonly occur late in football matches. Hamstring injury risk rises with age and fatigue. This study investigated eccentric hamstring strength and perceived hamstring soreness after a football match in younger and older players.